Depressive symptoms in children from 8 to 11 years old at the Mariano Lino Urquieta Moquegua Educational Institution, 2023 - Mamani Flores, Jenny Milagros (2024)
The objective is to determine the level of depressive symptoms in children aged 8 to 11 years at the Mariano Lino Urquieta Educational Institution Moquegua 2023. The study has a theoretical approach, cross-sectional, non-experimental design, and descriptive level. The population is 380 students, simple random sampling of 192 children, survey technique, the Children's Depression Questionnaire (CDS) by M. Lang and M. Tisher of 27 items was applied. The results of the evaluation of the level of depressive symptoms according to the age of the children, 39.1% are 9 years old, 37.5% are 10 years old, 15.1% are 8 years old, and 6.3% are 11 years old. Regarding gender, 53.1% are from the boy’s group and 44.8% are girls. Due to its dimensions, 92.20% of children present an average level of depressive symptoms of dysphoria and 65.6% present an average level of negative self-esteem. It is concluded that there is a significant predominance of the average level of depressive symptoms, which covers 78.90% of the total number of children aged 8 to 11 years.